Analytical Modelling of Software and Hardware Switches with Internal Buffer in Software-Defined Networks. (15th June 2019) - Singh, Deepak; Ng, Bryan; Lai, Yuan-Cheng; Lin, Ying-Dar; Seah, Winston K.G.
Abstract: OpenFlow supports internal buffering of data packets in Software-Defined Networking (SDN) switch whereby a fraction of data packet header is sent to the controller instead of an entire data packet. This internal buffering increases the robustness and the utilization of the link between SDN switches and the controller by absorbing temporary burst of packets which may overwhelm the controller. Existing queuing models for an SDN have focused on the switches that immediately sends packets to the controller for decisioning, with no existing models investigating the impact of the internal buffer in SDN software and hardware switches. In this paper, we propose a unified queueing model to characterise the performance of SDN software and hardware switches with the internal buffer. This unified queueing model is an analytical tool for network engineers to predict a delay and loss during SDN deployments in delay and loss sensitive environments. Our results show that a hardware switch achieves up to 80% lower average packet transfer delay and 99% lower packet loss rate at the cost of requiring up to 50% more queue capacity than a software switch. The proposed models are validated with a discrete event simulation, where the error between 0.6% and 2.8% was observed for both average packet transfer delay and average packet loss rate. Moreover, a hardware switch outperforms a software switch with increasing number of hosts per switch suggesting that a hardware switch has better scalability. We use the insights from the model to develop guidelines that help network engineers decide between a software and hardware switch in their SDN deployments. Graphical abstract: Image 1 Highlights: We propose a unified queues model for hardware and software SDN switch with internal buffer. Hardware switch achieves up to 80% lower delay, 99% lower packet loss rate, and 50% more queue capacity than software switch. Hardware switch outperforms software switch with an increasing number of hosts per switch.